2022
DOI: 10.1364/oe.448448
|View full text |Cite
|
Sign up to set email alerts
|

100-m/3-Gbps underwater wireless optical transmission using a wideband photomultiplier tube (PMT)

Abstract: In this paper, a wideband photomultiplier tube (PMT)-based underwater wireless optical communication (UWOC) system is proposed and a comprehensive experimental study of the proposed PMT-based UWOC system is conducted, in which the transmission distance, data rate, and attenuation length (AL) is pushed to 100.6 meters, 3 Gbps, and 6.62, respectively. The receiver sensitivity at 100.6-meter underwater transmission is as low as -40 dBm for the 1.5-Gbps on-off keying (OOK) modulation signal. To the best of our kno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(15 citation statements)
references
References 34 publications
0
15
0
Order By: Relevance
“…Apart from the link configuration optimization to mitigate the PAT issues in the underwater optical channel, creative solutions in the evolution of optical receivers can boost the performance of the optical IoUT systems. Ultra-sensitive detectors are widely applied in UWOC systems for long-distance sensing, such as APD [3], [4], MPPCs [111], and PMTs [5]. High-sensitivity APD can amplify the received photons, but its noise floor limits the SNR.…”
Section: Optimization On Receivers For Alleviating Underwater Link Al...mentioning
confidence: 99%
“…Apart from the link configuration optimization to mitigate the PAT issues in the underwater optical channel, creative solutions in the evolution of optical receivers can boost the performance of the optical IoUT systems. Ultra-sensitive detectors are widely applied in UWOC systems for long-distance sensing, such as APD [3], [4], MPPCs [111], and PMTs [5]. High-sensitivity APD can amplify the received photons, but its noise floor limits the SNR.…”
Section: Optimization On Receivers For Alleviating Underwater Link Al...mentioning
confidence: 99%
“…Underwater wireless optical communication (UWOC) has the advantages of high data rate and low latency, but with the shortcomings of strict link alignment and limited transmission distance [1][2][3][4] . The blue laser diode (LD), with high power, is gradually becoming the mainstream as the light source in the long-distance UWOC system [5][6][7][8][9][10] . Besides, many researchers employed high-sensitivity optical detectors such as a multi-pixel photon counter (MPPC), single-photon avalanche diode (SPAD), and photomultiplier tube (PMT) as receivers to detect weak optical signals [6][7][8][9][10][11] .…”
Section: Introductionmentioning
confidence: 99%
“…The blue laser diode (LD), with high power, is gradually becoming the mainstream as the light source in the long-distance UWOC system [5][6][7][8][9][10] . Besides, many researchers employed high-sensitivity optical detectors such as a multi-pixel photon counter (MPPC), single-photon avalanche diode (SPAD), and photomultiplier tube (PMT) as receivers to detect weak optical signals [6][7][8][9][10][11] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2018, a light-emitting diode (LED) based system developed by Lu et al achieved a data rate of 205 Mbps in the sea environment [2]. In 2021, Fei et al experimentally demonstrated a laser diode (LD) based 3 Gbps UWOC over 100 meters in a water tank [3]. Although the effective transmission distance of optical signals is relatively short, this is acceptable for mobile platforms, such as autonomous underwater vehicles (AUVs), remotely operated vehicles (ROVs), and underwater gliders.…”
Section: Introductionmentioning
confidence: 99%